Assessing the effect of empathy-enhancing interventions in health education and training: a systematic review of randomised controlled trials. Issue 9 (25th September 2020) - Winter, Rachel; Issa, Eyad; Roberts, Nia; Norman, Robert I; Howick, Jeremy
Abstract : Objective: To estimate the effect of empathy interventions in health education and training from randomised controlled trials (RCTs). Methods: MEDLINE, PsycINFO, EMBASE, CINAHL and Cochrane databases were searched from inception to June 2019 for RCTs investigating the effect of empathy-enhancing interventions in medical and healthcare students and professionals. Studies measuring any aspect of 'clinical empathy' as a primary or secondary outcome were included. Two reviewers extracted data and assessed the risk of bias of eligible studies using the Cochrane Risk of Bias Tool. Random effects meta-analyses of the impact of empathy training on participants' empathy levels were performed. Results: Twenty-six trials were included, with 22 providing adequate data for meta-analysis. An overall moderate effect on participant empathy postintervention (standardised mean difference 0.52, 95% CI 0.36 to 0.67) was found. Heterogeneity across trial results was substantial (I 2 =63%). Data on sustainability of effect was provided by 11 trials and found a moderate effect size for improved empathy up until 12 weeks (0.69, 95% CI 0.23 to 1.15), and a small but statistically significant effect size for sustainability at 12 weeks and beyond (standardised mean difference 0.34, 95% CI 0.11 to 0.57). In total, 15 studies were considered to be either unclear or high risk of bias. The quality of evidence of included studies was low. Conclusion: Findings suggest that empathy-enhancing interventions can be effective at cultivating and sustaining empathy with intervention specifics contributing to effectiveness. This review focuses on an important, growing area of medical education and provides guidance to those looking to develop effective interventions to enhance empathy in the healthcare setting. Further high-quality trials are needed that include patient-led outcome assessments and further evaluate the long-term sustainability of empathy training. Protocol registration number: PROSPERO (CRD42019126843).